1974
DOI: 10.1104/pp.53.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Ethylene on Potato Dormancy and Sprout Growth

Abstract: Dormant potato tubers (Solanum tuberosum L.) of two cultivars were treated with various concentrations of ethylene gas for various exposure periods. As has been shown by others, ethylene caused a rapid but transient increase in respiration rate, which appeared to be independent of any effects on dormancy. All concentrations tested caused accelerated sprouting, 2 microliters per liter being the most effective. Ethylene exerts a dual effect on potato tubers: it markedly shortens the duration of rest, but it inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
6

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 19 publications
2
52
0
6
Order By: Relevance
“…Subsequent studies identified a number of bioactive compounds in the volatile fraction, including benzothiazole, diphenylamine, and 1,4-and 1,6-dimethylnaphthalene (Meigh et al, 1973). Although ethylene was also identified as a component of the volatile fraction, its involvement in volatile-induced sprout growth inhibition was discounted because of its very low concentration in the total volatile fraction and its relatively poor bioactivity (Burton and Meigh, 1971;Rylski et al, 1974). Given the low rates of ethylene evolution and the ephemeral nature of the ethylene requirement, it is likely that without the use of the in vitro tuberization system and the specific inhibitors of ethylene action, the role of endogenous ethylene in potato tuber dormancy regulation would have again escaped detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies identified a number of bioactive compounds in the volatile fraction, including benzothiazole, diphenylamine, and 1,4-and 1,6-dimethylnaphthalene (Meigh et al, 1973). Although ethylene was also identified as a component of the volatile fraction, its involvement in volatile-induced sprout growth inhibition was discounted because of its very low concentration in the total volatile fraction and its relatively poor bioactivity (Burton and Meigh, 1971;Rylski et al, 1974). Given the low rates of ethylene evolution and the ephemeral nature of the ethylene requirement, it is likely that without the use of the in vitro tuberization system and the specific inhibitors of ethylene action, the role of endogenous ethylene in potato tuber dormancy regulation would have again escaped detection.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the concentration and duration of exposure, exogenous ethylene can either hasten or delay tuber sprouting. Relatively shortterm (less than 3 d) exposure to ethylene results in the premature termination of tuber endodormancy, whereas long-term or continuous exposure to similar concentrations of ethylene inhibits subsequent sprout growth (Rylski et al, 1974). Temporary treatment with exogenous ethylene has also been reported to stimulate the sprouting of partially dormant tubers (Alam et al, 1994).…”
mentioning
confidence: 99%
“…Conflicting data have been published concerning its role during later stages of dormancy and sprouting as summarised by Suttle (2004bSuttle ( , 2007. In brief, exogenous application could either shorten or delay the dormancy period depending on the duration of treatment and the concentration applied (Rylski et al 1974;Prange et al 1998). Previously, Suttle (2009) reported that neither ethylene application nor stimulation of endogenous biosynthesis was effective in bud break or sprout growth.…”
Section: Hormonal Controlmentioning
confidence: 99%
“…maximum tuber sprouting percentage was observed and it may be because eCC broke the dormancy of tubers and also reduced the production of growth inhibiting hormone abscisic acid (AbA) (el-Antably et al 1967;Alam et al 1994). it has been reported that short-term ethylene treatment can prematurely terminate tuber dormancy whereas continuous treatment results in delay in sprout growth inhibition (Rylski et al 1974). Similarly, treatment with ethylene releasing agents has been reported to either hasten or delay sprouting (Cvikrova et al 1994).…”
Section: Pre-harvest Effects Of Ecc Number Of Days Required For Seed mentioning
confidence: 99%